Analysis of ocean tide loading displacements by GPS kinematic precise point positioning: a case study at the China coastal site SHAO. Issue 365 (4th March 2019) - Zhao, H.; Zhang, Q.; Tu, R.; Liu, Z.
Abstract : Ocean tide loading (OTL) displacement amplitudes and phase lags of SHAO site are estimated by global positioning system (GPS), kinematic precise point positioning (PPP) and spectral analysis using 19 years of continuous GPS observations. In kinematic PPP, the 66 additional harmonic displacement parameters are replaced by the three time-varying displacement parameters without a priori modelled OTL displacements. By comparing the results with predictions from hybrid regional/global models, we are able to demonstrate that GPS/model agreements are at the level of 0.2 mm (horizontal) and 0.6 mm (vertical) for the four lunar constituents, 0.4 mm (horizontal) and 1.35 mm (vertical) for the four solar/sidereal constituents, and 0.2 mm (horizontal) and 0.3 mm (vertical) for the three long-period constituents. Finally, we conclude that GPS-derived lunar constituents can substitute for the model corrections in GPS data processing and the accuracy of GPS-derived solar/sidereal constituents needs to be improved by further studies.